Women's Right to Work: A Jurisprudential Study Compared to the UAE Labor Relations Regulation Law - Deif Allah, Alia Ahmad (Dirasat: Shari'a and Law Sciences, 2021)
This research dealt with the legal provisions that apply to women's work and the legal evidence in sharia that permitted them to work by regulations which were safeguards for them. This research shows that Islamic legislation was the first to take care of women and protect them. This study adopted the descriptive approach by extrapolating the issues and standing on their legal provisions and evidence, then comparing them with what is stipulated by the UAE Labor Relations Regulation Law and the CEDAW agreement. It also pointed to take into consideration the legal objectives of sharia that are represented in saving life and posterity in some of the jurisprudential issues related to their work, as the provisions in sharia are distinguished from the provisions of the UAE labor relations act and the convention on the elimination of all forms of discrimination against Women. The researcher recommends the need to familiarize Muslim women with the system of Islamic legislation that has elevated the status of women by caring for and protecting them concerning their rights at work. He recommended the need for equality in maternity and lactation leave in labor laws, as it is a humanitarian requirement and a necessity for protecting women and children.